Healthy Streets: Adopting International Benchmarks in Medium Density Cities. Issue 4 (2nd October 2021) - McIntosh, Jacqueline; Marques, Bruno; Smith, Melody; Rodgers, Maria; Morgan, Abigail
ABSTRACT: Globally, large cities are implementing guidelines to ensure that environment, economics and sociality are at the forefront of urban design. Promotion of healthier streets has created new opportunities for social and commercial interaction and more inclusive outcomes. However, while most megacity streets share commonalities, the streets in medium-density urban centres do not always share the same problems and opportunities. Following the London Healthy Street programme, interviews were conducted on four inner-suburban Wellington, Aotearoa-New Zealand streets. Findings highlight the impacts of changing demographics and street functionality and indicate that urban scale can be a factor in opportunity for innovative and user-friendly street design.